Kreativitas Tata Cahaya Moderen Dalam Pertunjukan Wayang Kulit Bali Masa Kini - Sudiana, I Ketut (CV RIFAINSTITUT, 2022)
The problem of puppet show lighting in the puppet show is a very important element to be carefully considered as it is a medium in projecting shadow puppets on the screen.Because lighting is very influential ( the result of the projected shadow) that project the identity of Balinese leather puppet figures, which contain aesthetic and symbolic values. In principle, the use of lighting in puppet shows should be able to produce a high carrying capacity, not merely the modern practicality but it also able to illuminate according to the form of puppets in a surreal form.It also supports the expected dramatic atmosphere, such as scenery or background depiction,in order to anticipate the shift in the thoughts of contemporary puppet viewers who tend to be realists. In line with the objective of this research which is to produce the anatomical shape of Balinese Wayang Kulit with an ideal proportions of electric lighting. It also aims to produce a scenery that is in accordance to the style of Balinese Wayang Kulit which is not realistic. The method used is the Practice-based Research method , a creating and studying works of art based method. This practice-can produce the ideal shape and anatomy of wayang and the harmony between scenery and wayang.